O sub-relato e fatores correlacionados ao uso de cocaína e maconha no terceiro trimestre de gestação em adolescentes grávidas - Bessa, Marco Antonio [UNIFESP] (2010)
Introduction: The use of drugs by pregnat adolescents is a serious problem of public health because it can harm the mother and the newborn. So, the correct identification of the cases and the correlates of use of drugs in this population are important for the comprehension of this condition, for the identification of adolescents in high risk for this situation and for helping the development of public politics of prevention and correct treatment of these cases. Aims: 1) To check the validity of the self-report of drug use by pregnant adolescents, by comparing their responses to a structured interview about their use of cocaine and marijuana during the pregnancy with an analysis of their hair. 2) To investigate the association of cocaine and marijuana use during adolescent pregnancy in São Paulo, Brazil, with psychiatric disorders, social status and sexual history. Method: One thousand pregnant adolescents were evaluated using the Composite International Diagnostic Interview, and sociodemographic and socio-economic questionnaire at the obstetric center of a public hospital in São Paulo, Brazil. Hair sample was collected for analysis. Results: Hair analysis detected the use of cocaine and/or marijuana in the third trimester of pregnancy in 60 (6%) patients. 40 (4%) patients used only marijuana, 17 (1.7%) used only cocaine, and 3 (0.3%) used both drugs. None of the patients had reported the use of these substances in their interviews with healthcare professionals. The following are associated with cocaine and/or marijuana use during the third trimester of the pregnancy: Being younger than 14 years of age, having a history of more than 3 sexual partners, and having psychiatric disorders, specifically, bipolar disorder, post-traumatic stress disorder, and somatoform disorder. Conclusion: Although the prevalence of the use of drugs during pregnancy is significant despite consistent evidence about the compromise of the neurobehavioral development of the newborns that are exposed to drugs during the prenatal period, drug use is frequently not reported. Therefore, more sensitive methods of detection should be used so that appropriate medical and psychosocial interventions can be implemented for the mothers as well as for their children. In early adolescence pregnancy, having 3 or more sexual partners in life for this population is significantly associated with the use of cocaine or marijuana during gestation. This association suggests that specific intervention programs should target these young women.